Transactional quality, relational quality, and consumer e-loyalty: Evidence from SEM and fsQCA. Issue 6 (December 2016) - Fang, Jiaming; Shao, Yunfei; Wen, Chao
Highlights: We integrate transactional and relational perspective factors in the same model. fsQCA reveals several equifinal configurations leading to e-loyalty. Consumer heterogeneity results in dissimilar configurations leading to e-loyalty. Satisfaction is a necessary but not sufficient condition leading to e-loyalty. The results reveal the causal complexities of repurchasing decision. Abstract: Customer loyalty plays a vital role in the success of e-commerce. Based on loyalty development process framework proposed by Oliver (1997), we propose an integrated model including factors derived from both transactional and relational perspectives to investigate the formation mechanism of consumer loyalty to online vendors in the context of e-tailing. Structural equation modeling (SEM) and fuzzy set qualitative comparative analysis (fsQCA) were used to analyze the survey data collected from 664 online shoppers. SEM reveals the net effect of the antecedents on e-loyalty; while fsQCA provides the combinations of causal recipes associated with the loyalty. The results from fsQCA reveal that none of the sub-constructs of transactional quality or relational quality is sufficient conditions for e-loyalty. Moreover, consumer heterogeneity in term of gender, age, and shopping motivation results in dissimilar configurations to achieve e-loyalty. The research results provide insights to both theory and practice.